A comprehensive study of laser irradiated hydrothermally synthesized 2D layered heterostructure V2O5(1−x)MoS2(x) (X = 1–5%) nanocomposites for photocatalytic application - Jameel, Muhammad Hasnain; Yasin, Aqeela; Samia; Mayzan, Mohd Zul Hilmi; Roslan, Muhammad Sufi; Esa, Fahmiruddin; Agam, Mohd Arif; Mohd Zaid, Mohd Hafiz; Althubeiti, Khaled; Aljohani, Mohammed (Walter de Gruyter GmbH, 2024)
It has been studied that both two-dimensional (2D) MoS2 and V2O5, which are classified as transition metal dichalcogenides and transition metal oxides, are good photocatalyst materials. For this purpose, the hydrothermal method was practiced to synthesize V2O5(1−x)MoS2(x) (X = 1–5% w/w) nanocomposites with different 1–5% w/w weight percent of MoS2 as a prominent photocatalyst under laser irradiation for 2, 4, 6, 8, and 10 min to tune photocatalytic degradation of industrial wastage water. The surface of the 2D molybdenum nanolayered matrix was efficaciously decorated with V2O5 nanoparticles. The crystal phase and layered structures of the V2O5(1−x)MoS2(x) (X = 1–5% w/w) nanocomposites samples were verified by X-ray diffraction and scanning electron microscopy, atomic force microscopy, X-ray photoelectron spectroscopy respectively. In the range of the UV visible spectrum, the increment in light absorption from 3.6 to 14.5 Ω−1 cm−1 with an increase of active surface from 108 to 169 μm2 with increased MoS2 doping percentage. Furthermore, dielectric findings like the complex dielectric function, tangent loss, electrical conductivity, quality factors, and impedance of V2O5(1−x)MoS2(x) (X = 1–5% w/w) nanocomposites are studied. According to photoluminescence studies, the intensity of peaks decreases when laser irradiation time and doping percentages of MoS2 are increased. As a result, a small peak indicates a decrement rate of electron–hole pair recombination, which increases the capacity for separation. Thermo-gravimetric analysis and differential thermal analysis results revealed that weight loss decreased from 0.69 to 0.35 mg and thermal stability increased with increased doping concentrations. Methylene blue was degraded in 150 min, proving that the prepared MoS2-doped V2O5 material was a stable and economically low-cost nanocomposite for photocatalytic activity.